Trio ABG Model and Competitive Advantages in Growing Creative Industry in East Java - Gendut Sukarno; Sri Mulyaningsih; Lia Nirawati; Mei Retno Adiwaty (Nusantara Science and Technology Proceedings)
ASEAN Economic Society (MEA) era initiated in 2015 brought opportunity and challenge as well for Indonesian economic. As MEA enacted in the end of 2015, ASEAN member countries experience free flow of goods, services, investment and educated manpower from and to respective countries. From 14 creative economic sectors as listed in Presidential Instruction (Inpres) Number 6 Year 2009 concerning Creative Economic Development, there is one poor creative industry subsector, namely ‘Exhibition Art’, in which such subsector only contribute 0.10% from entire creative industries. TRIO ABG or frequently referred to as Triple Helix, which is synergy between Business Government, is one of concept in increasing creative industry growth. In addition, creative industry establishment also determined from such creative industry competitive advantages. This research aimed to review TRIO ABG contribution and Competitive Advantages against exhibition art creative industry development in East Java. Population in this research were entire creative industry owner/management from 14 creative industry sectors. Sample in this research were 42 owners/management of ‚Exhibition Art? creative industry sub-sector. Partial Least Square (PLS) were analysis technique used in this research, which is analysis alternative method with variance-based Structural Equation Modeling (SEM). Research result showed that TRIO ABG still unable to provided contribution for exhibition art creative industry in East Java. Such three helix roles actually exist, but it was highly minimum and not synergized yet. Likewise, competitive advantages on exhibition art creative industry in East Java still unable to become competitive advantage that could compete with other industries.